The genus Argopistes Motschulsky from Japan and Taiwan, with descriptions of three new species from Taiwan (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Chi-Feng Lee; Ming-Yao Chiang; Haruki Suenaga (ZooKeys, 2024)
Four previously described species of Argopistes are recognized and redescribed from Japan and Taiwan: A. biplagiatus Motschulsky, 1860, A. rufus Chen, 1934, A. tsekooni Chen, 1934, and A. unicolor Jacoby, 1885. Three new species from Taiwan, A. jungchani sp. nov., A. tsoui sp. nov., and A. yuae sp. nov., are described. Descriptions of species include illustrations of aedeagi, antennae, gonocoxae, abdominal ventrite VIII, and spermathecae. Argopistes rufus Chen, 1934, stat. nov. is raised to species status from a variety of A. biplagiatus Motschulsky, 1860. Argopistes coccinelliformis Csiki, 1940, syn. nov. and A. ryukyuensis Shigetoh & Suenaga, 2022, syn. nov. are proposed as junior synonyms of A. rufus Chen, 1934 Lectotypes are designated for A. undecimmaculata Jacoby, 1885, A. unicolor Jacoby, 1885, and A. biplagiatus var. rufus Chen, 1934.